Knowledge of native valve anatomy is essential in follow-up of patients after aortic valve replacement. (15th December 2016) - Cozijnsen, Luc; van der Zaag-Loonen, Hester J.; Cozijnsen, Martinus A.; Braam, Richard L.; Heijmen, Robin H.; Mulder, Barbara J.M.
Abstract: Background: After aortic valve replacement (AVR), bicuspid aortic valve (BAV) patients continue to be at risk of aortic complications. Therefore, knowledge of native valve anatomy is important for follow-up. We aimed to determine the extent of which the presence of BAV disease is known in a regional post-AVR population. Methods: The Electronical Medical Record system was used to collect all patients under follow-up after AVR. We documented their clinical data and used the operative report to determine valve phenotype; lacking reports were retrieved. Results: We identified 560 patients who underwent AVR between 1971 and 2012, with a median of 6.2 years follow-up postoperatively. Mean age at surgery was 66 years (SD13.2 years), and 319 patients (57%) were male. In 29 cases (5%), an operative report was not available and in 85 patients (16%) the report lacked a description of valve phenotype. In 446 patients, a surgeon's description of native valve was available: 299 patients (67%) had tricuspid aortic valve, 140 (31%) BAV, and 3 (1%) quadricuspid aortic valve. In 4 patients (1%) the description was non-conclusive. In 66/140 BAV patients the surgeon's diagnosis was not reported back to the referring cardiologist, which corresponded with 12% of all 560 AVR patients. Another 21% of these 560 lacked a clear description of native valve anatomy: no report, no native valve description or an unclear valve description. Conclusions: Native valve anatomy was not known in one-third of AVR patients under follow-up, which included almost half of the BAV patients. This lack of knowledge withholds patients from appropriate ascending aorta surveillance.